Ribavirin suppresses erythroid differentiation and proliferation in chronic hepatitis C patients. Issue 6 (15th August 2013) - Ronzoni, L.; Aghemo, A.; Rumi, M. G.; Prati, G.; Colancecco, A.; Porretti, L.; Monico, S.; Colombo, M.; Cappellini, M. D.
Summary Combination therapy with pegylated interferon (pegIFN) plus ribavirin (RBV) is the standard of care for chronic hepatitis C. One of the major treatment‐related side effects is anaemia, attributed to RBV‐induced haemolysis. However, haemolysis biomarkers are not present in all patients supporting the existence of other pathogenetic mechanisms. We studied the role of RBV in inducing haemolysis and its effects on erythropoiesis. In 18 hepatitis C virus (HCV) genotype 2 patients treated with pegIFN‐alpha‐2a (180 mcg/week) plus RBV (800 mg/day) for 24 weeks and in 10 hepatitis B virus (HBV) patients treated with pegIFN‐alpha‐2a (180 mcg/week) for 48 weeks, haemolysis was assessed by serum LDH, haptoglobin and reticulocyte count. Erythropoiesis was evaluated both ex vivo, analysing the clonogenic activity of patients' erythroid progenitors, as well as in vitro adding pegIFN and RBV to liquid cultures obtained from CD34+ cells of healthy volunteers. The majority of patients developed anaemia; the week 4 mean haemoglobin decrease was greater in HCV than in HBV patients (1.7 vs 0.47 g/dL, P = 0.01). Only three HCV patients (17%) and no HBV patients showed signs of haemolysis. The 15 nonhaemolytic HCV patients and all HBV patients showed a delay in erythroid differentiation, with a reduction in colony number and a relative increase in undifferentiated colony percentage. Haemolytic HCV patients had an increase in colony number at week 4 of therapy. In vitro, erythroid cell proliferation and differentiation were inhibited by both pegIFN and RBV. Both pegIFN and RBV have an inhibitory effect on erythroid proliferation and differentiation.